2019
DOI: 10.7577/seminar.3402
|View full text |Cite
|
Sign up to set email alerts
|

Teachers as users of ICT from the student perspective in higher education flipped classroom classes

Abstract: The use of information and communication technology (ICT) is important in today’s higher education. ICT has a central role in the skill set students are expected to master during their studies. The fast development of technology poses both possibilities and challenges for teachers. This paper is part of a larger project aimed at implementing the flipped classroom (FC) model and supporting ICT integration in higher education. In this project, teachers receive systematic support for implementing the FC mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…This study highlights the importance of clearly outlining the learning process of a flipped classroom for the students and the need for providing students with clear instruction and guidance. Also, as the flipped approach may be new for students, the more self-directed role of the students may cause challenges and pose demands for more support (e.g., Hyppönen et al, 2019 ; Sointu et al, 2019 ). Again, students need to be provided with the feeling that they are learning in a safe atmosphere as well as with a secure feeling for participating, bringing up their ideas, and asking for help whenever needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study highlights the importance of clearly outlining the learning process of a flipped classroom for the students and the need for providing students with clear instruction and guidance. Also, as the flipped approach may be new for students, the more self-directed role of the students may cause challenges and pose demands for more support (e.g., Hyppönen et al, 2019 ; Sointu et al, 2019 ). Again, students need to be provided with the feeling that they are learning in a safe atmosphere as well as with a secure feeling for participating, bringing up their ideas, and asking for help whenever needed.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there have been some good practices for using ICT to support the flipped courses. Sointu et al ( 2019 ) discovered that students perceived their teaching during a flipped course as having more positive views concerning the use of technology, while McNally et al ( 2017 ) found that students themselves preferred using technology to assist their learning over other aspects in the flipped classroom environment. Moreover, Davies et al ( 2013 ) found that a technology enhanced flipped classroom was more motivating and helped facilitate learning.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and colleagues (2014) found that FC can facilitate a safe and open learning atmosphere. FC also seems to improve teachers' content, pedagogical, and technological usage qualities from the student's perspective (Sointu et al, 2019b).…”
Section: Flipped Classroommentioning
confidence: 99%
“…Individual statements consisted of statements regarding how students viewed the FC approach: whether it suited them, whether they would prefer to study in a more traditional manner (e.g., Sointu et al, 2019b), and how motivating, meaningful, relevant, or challenging FC was for them (Sointu et al, 2020). Moreover, elements of usability (i.e., pre-materials, contact teaching, preparedness, use of time, support, interest, and quality) were investigated.…”
Section: Measures and Data Analysismentioning
confidence: 99%
“…ICT plays a central role in the skill set that students are expected to master during their studies. The rapid development of ICT presents both opportunities for students and teachers (Sointu et al, 2019 ; Zheng et al, 2020 ). In recent years, several new technologies with different pedagogical approaches supported by ICT have attracted attention.…”
Section: Introductionmentioning
confidence: 99%